Pretreatment synthetic magnetic resonance imaging predicts disease progression in nonmetastatic nasopharyngeal carcinoma after intensity modulation radiation therapy - Fan Yang; Haoran Wei; Xiaolu Li; Xiaoduo Yu; Yanfeng Zhao; Lin Li; Yujie Li; Lizhi Xie; Sicong Wang; Meng Lin (Insights into Imaging, 2023)
Key points 1. SyMRI showed excellent performance in predicting disease progression in NPC. 2. T1_Kurtosis and ADC were independent predictors of progression-free survival. 3. T1_Kurtosis was lower in the non-disease progression group than the disease progression group. 4. Combination of SyMRI, DWI, and clinical factors could improve the predictive performance.